MUTATION DETECTION OF MULTIDRUG-RESISTANT TUBERCULOSIS BY RT-PCR METHOD AS THE DIAGNOSTIC TOOL OF MDR-TB - Titta Novianti; alfero Putra Iryanto; feby feby; callista marsya; putri mega utami; febriana dwi wahyuni; henny saraswati; seprianto; adri nora; roaslein putri; nie nie; sabar pambudi (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2023)
Eight percent of tuberculosis (TB) cases worldwide are resistant to rifampicin, with mutations occurring in the rpoB and katG genes. It is necessary to develop a specific multidrug-resistant (MDR) diagnostic technique using the RT-PCR method in Indonesia to aid in rapid and accurate diagnosis. In-silico testing using SnapGene software resulted in the design of DNA primers for the katG and rpoB genes, plasmids, and specific probes. This study employed a cross-sectional design using 30 non-MDR-TB and MDR-TB samples from RSUD Sitanala, Tangerang Banten, which were tested for amplification of the katG and rpoB genes using Sybr green RT-PCR. Validity testing was conducted using specific probes for the katG and rpoB genes. The amplification results showed that MDR-TB samples and MDR-TB plasmids required a longer time compared to non-MDR-TB samples and non-MDR-TB plasmids. The Quantification Cycle (Cq) value in non-MDR-TB samples was lower than the Cq value in MDR-TB samples. A t-test revealed a significant difference in Cq values of the rpoB and katG genes between MDR-TB and non-MDR-TB patients (p-value < 0.005). These differences in Cq values indicate that the findings of this study can serve as an initial reference for the development of an RT-PCR-based diagnostic kit for MDR-TB.